Patient with obstructive sleep apnoea at the orthodontics practise – case report - Matuszkiewicz, Anna; Lasota, Agnieszka; Kiernicka, Katarzyna; Dunin-Wilczyńska, Izabella (Forum Ortodontyczne / Orthodontic Forum, 2018)
Obstructive Sleep Apnoea (OSA) is characterised by at least five 10-second episodes of apnoea or significant shallow breathing (hypopnoea), accompanied by a decrease in oxygen saturation of arterial blood by 2–4% per hour of sleep, with preserved or intensified respiratory muscle movements. In men OSA is most often diagnosed after the age of 40 years, in women – usually after the age of 50 years. The risk group includes patients diagnosed with being overweight or obese, cardiovascular diseases, hypertension, hypothyroidism, diabetes, asthma, allergies or congenital anomalies. Aim. The aim of the work was to present changes in the anatomy of structures of the facial skeleton in a 31-year-old orthodontic male patient with a mild form of sleep apnoea. Material. Material included: orthodontic records, EPWORTH sleepiness scale filled in by the patient, gypsum models, photographs (intra- and extraoral photographs) and radiological records (panoramic radiograph, lateral cephalogram) and results of polysomnography. Case report. The paper presents a case of a 31-year-old male patient without systemic diseases who reported for an orthodontic consultation due to tooth crowding. The analysis of the orthodontic documentation revealed a suspicion of sleep apnoea. A polysomnographic examination confirmed the presence of mild OSA. Conclusions. The analysis of a lateral cephalogram revealed changes in the length of the soft palate, width of the upper respiratory tract and a position of the hyoid bone. The EPWORTH sleepiness scale indicated the presence of excessive sleepiness, and the polysomnographic examination confirmed the occurrence of mild OSA. Sleep apnoea may affect relatively young people, with a normal body weight and without any systemic diseases. Therefore orthodontists’ awareness about risk factors and sleep apnoea symptoms should be used in everyday practice. (Matuszkiewicz A, Lasota A, Kiernicka K, Dunin-Wilczyńska I. Patient with obstructive sleep apnoea at the orthodontist’s – case report. Orthod Forum 2018; 14: 309-20).